Catholic Neutrality: The Peace of Henri Bourassa - Keelan, Geoff (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2011)
One-time Liberal Member of Parliament, Henri Bourassa (1868-1952) was also a member of the Quebec provincial legislature, French Canadian nationalist and editor of Le Devoir from 1910 to 1932. His enduring career lasted over five decades, during which he discussed a wide range of domestic and political issues. During the First World War, historians have traditionally acknowledged his powerful domestic presence, such as over French language rights, the Conscription Crisis of 1917, or during the Easter riots of 1918. As a result, few scholars have commented on his broad-ranging and critical analyses of the international situation in Europe. This article uses Bourassa’s discussion of the various peace proposals during the war to better understand his ability to engage and understand complex international events. It examines his reaction to the German peace proposal of December 1916, President Wilson’s peace note of December 1916, Lord Lansdowne’s letter of November 1917 and the Papal peace initiatives. It concludes that although Bourassa was greatly influenced by his Catholic religious beliefs, he ultimately displayed an intelligent understanding of the war that far exceeded many other contemporary Canadian observers.